2005
DOI: 10.1902/jop.2005.76.9.1450
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clinical Attachment Loss in Adolescents in Santo Domingo, Dominican Republic

Abstract: We conclude that clinical attachment loss is common in adolescents in Santo Domingo, Dominican Republic, suggesting the necessity for improved standards of prevention, diagnosis, and treatment of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
1
23
1
5
Order By: Relevance
“…Associations of gender and ethnic background with gingival recession have been reported (Gorman 1967, Albandar & Kingman 1999, Susin et al 2004, Collins et al 2005, Abrahamsson et al 2006). Our data revealed no association of either factor on inter‐dental papilla appearance, with the following exception: papilla height was greater for males than females ( p <0.05), which may have been due to larger tooth size in the males.…”
Section: Discussionmentioning
confidence: 99%
“…Associations of gender and ethnic background with gingival recession have been reported (Gorman 1967, Albandar & Kingman 1999, Susin et al 2004, Collins et al 2005, Abrahamsson et al 2006). Our data revealed no association of either factor on inter‐dental papilla appearance, with the following exception: papilla height was greater for males than females ( p <0.05), which may have been due to larger tooth size in the males.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, os dados relacionados às condições periodontais de adultos jovens ainda são escassos 2,11 . O foco dos estudos sobre doença periodontal está voltado para populações de meia-idade ou idosas, nas quais a severidade da doença é elevada; diversamente, os estudos em indivíduos jovens costumam se concentrar na investigação das formas agressivas de periodontite [11][12][13] . A doença periodontal não acomete apenas adultos com idade acima de 35 anos.…”
Section: Introductionunclassified
“…Considerandose o caráter cumulativo de destruição dos tecidos periodontais, torna-se imprescindível a compreensão das suas características epidemiológicas e clínicas no início do curso da doença. Esses dados devem servir de base para intervenções apropriadas, voltadas à prevenção da sua progressão e ao seu tratamento precoce 12,14 .…”
Section: Introductionunclassified
“…Prospective studies on periodontal disease progression among adolescents and young adults indicated that subjects showing destructive disease at early ages have a higher risk for developing future clinical attachment and bone loss 9,13,14 . Among subjects diagnosed with early‐onset forms of disease and low socioeconomic status, periodontal deterioration seems to be more evident at previously affected sites 3,4,16 . Deterioration in the periodontal status involves an increase in extension rates (increased number of sites with CAL and BL) and severity rates (additional CAL and BL at previously affected sites) 3,16,18 …”
mentioning
confidence: 99%
“…Among subjects diagnosed with early‐onset forms of disease and low socioeconomic status, periodontal deterioration seems to be more evident at previously affected sites 3,4,16 . Deterioration in the periodontal status involves an increase in extension rates (increased number of sites with CAL and BL) and severity rates (additional CAL and BL at previously affected sites) 3,16,18 …”
mentioning
confidence: 99%